A classic examination of fluvial processes and forest patterns: Victor Ernest Shelford's (1954) 'Some Lower Mississippi Valley Flood Plain Communities: Their Age and Elevation'. Ecology 35(2): 126–142.1. (December 2014) - Meitzen, Kimberly M.
The study of the interaction between fluvial processes and forest community patterns owes elements of its origins to the research of Shelford (1954) on the Mississippi River valley. Shelford (1954) is a classic for many reasons; three highlighted here are its role of establishing a methodology for applying historical resources for long-term research studies, its influence on developing conceptual models of forest succession relative to multiple controlling factors, and its recognition of the rapid and extensive impact of human activities on altering natural land-cover patterns and the important role of analog forests for management and conservation. References to Shelford (1954) within the literature have increased every year since its publication and I believe its presence among varied disciplines will continue.